Impact of Destination Images and E-WOM on Urban Millenial Decision to Visit Tourism Potential City - Akbara, Anisa Zahwa; Suryantari, Yulita (Lasigo Akademia Indonesia, 2024)
Tourism potential in Serang City is almost eliminated and forgotten along with the city’s continuous expansion. The role of urban millennials in promoting tourism is now important. Therefore, researchers used urban millennials as respondents in this study. By using SEM analysis with the SmartPLS application, this research was conducted to determine destination image preferences from millennial tourists in Serang City and their influence on e-WOM and the decision to visit. The results indicated support for affective image, price image, and travel motivation positively influence e-WOM. However, e-WOM does not appear to have a significant positive influence on the decision to visit. Additionally, cognitive image is the only factor that positively influences the decision to visit directly. The proposed mediating role of e-WOM in the relationship between destination image with the decision to visit is not supported. The findings of this study offer important factors for the destination marketers, policymakers, and businesses of a potential tourism city, in this case Serang City, to consider when developing a specific marketing strategy for this market segment (urban millennials). In addition, the results of this study provide a better understanding of the urban millennial perspective on their decision to visit cities with tourism potential.